Accommodating Resistance: Unionization, Gender, and Ethnicity in Winnipeg’s Garment Industry, 1929–1945 - Giesbrecht, Jodi (Urban History Review / Revue d'histoire urbaine)

(untitled) (Urban History Review / Revue d'histoire urbaine, 2010)
This article examines the culturally particular and gendered ways in which Jewish immigrant women in the garment industry negotiated their new Canadian urban environments by participating in labour protest, indicating how the site of the strike was one structured by gender and ethnicity as well as by class. Canada’s urban space both facilitated immigrant women’s integration into society by enabling their interaction with Canadian political and economic structures and encouraged their retention of culturally particular ways of life by providing sites and spaces for politically charged gatherings that not only reinforced these workers’ ethnic traditions but also put their status as militant women on public display. These women strikers’ accommodation and resistance to Canadian society was also affected by Anglo Canadians’ representations of them, by shifting unionization tactics—from radical to conservative—and by social constructions of gender, ethnicity, and class.